Oxidative stress as a biomarker for monitoring treated celiac disease. Issue 6 (June 2018) - Moretti, Sarah; Mrakic‐Sposta, Simona; Roncoroni, Leda; Vezzoli, Alessandra; Dellanoce, Cinzia; Monguzzi, Erika; Branchi, Federica; Ferretti, Francesca; Lombardo, Vincenza; Doneda, Luisa; Scricciolo, Alice; Elli, Luca
Abstract : Introduction: : High levels of reactive oxygen species (ROS) and impaired antioxidant defense systems lead to oxidative stress (OxS) and tissue injury in different intestinal and extra intestinal conditions, including celiac disease (CD). The aim of the present study was to investigate the role and potential use of ROS and other biomarkers of OxS in the clinical management of CD. Methods: : We collected duodenal specimens and blood samples from naïve patients (N‐CD), patients on a gluten free diet (GFD) including responders (CD‐GFD) and non‐responders (NRCD).We measured plasmatic ROS production (electron paramagnetic resonance, EPR), lipid peroxidation (thiobarbituric acid‐reactive substances, TBARS), protein oxidation (protein carbonyl, PC), total antioxidant capacity (TAC), nitric oxides and glutathione (GSH) in erythrocytes. Results: : Fifty‐four patients affected by CD were enrolled (17 N‐CD, 18 CD‐GFD and 19 NRCD; 44 F; age 44 ± 13 years). A significant increase of plasmatic OxS biomarkers (ROS, peroxidated lipids, oxidized proteins, and nitrate concentrations) and decrease of antioxidant species (TAC and GSH levels) were found in NRCD and N‐CD compared to CD‐GFD. Comparably, a significant direct relationship between the severity of duodenal atrophy, ROS production rates and TBARS was found; conversely, TAC and GSH presented an inverse correlation. Discussion: : OxS is involved in CD tissue damage and correlates with the degree of duodenal atrophy. These findings suggest the possible role of OxS biomarkers as indicators of CD activity during the clinical follow‐up.